Heavy metals (Fe, Cu, and Cr) removal from wastewater by moringa oleifera press cake - Ali, Eman N.; Hong, Tien Seng (EDP Sciences, 2018)

(untitled)
The consumption of water nowadays is increasing and the wastewater from variety of industry and domestic are increasing as well. If this wastewater is being untreated, it will be wasted and the chemicals inside the water especially heavy metal are harmful to the living organism. There are few conventional method used to treat the wastewater but most of them are costly, hence, natural coagulant is introduced in this study. One of the multipurpose tree Moringa oleifera, (MO) which is environmental friendly and low cost become a choice for removal of heavy metal from wastewater. The Moringa oleifera press cake (MOPC) are able to remove the heavy metal but the removal efficiency for different metals need to be investigated. Therefore, experiment on heavy metal removal by Moringa oleifera press cake was conducted. The wastewater samples and MOPC were collected from Balok River, Kuantan and Mitomasa Sdn. Bhd, Kuala Lumpur respectively. MOPC was immersed in distilled water to remove the oil and different concentration of MOPC solution were made. Jar test were carried out with different concentration of MOPC solution. The initial and final heavy metal (Fe, Cu, and Cr) concentration were measured by Atomic Absorption Spectrometer and the removal percentage was calculated. The MOPC removed 69.99% Fe, 88.86 % Cu and 93.73% Cr at optimum concentration of 10000 ppm, 5000 ppm and 15000 ppm, respectively. The MOPC also reduced 34.94% of COD and 81.6 % of turbidity. However, BOD of wastewater increased from 9.0 ppm to 18.3 ppm. The pH values was not changed with the addition of MOPC. The removal of heavy metal was increased proportionally with MOPC concentration until optimum removal was obtained.